Brachial artery vasodilatory response and wall shear rate determined by multigate Doppler in a healthy young cohort - Aizawa, Kunihiko (J Appl Physiol (1985), 2018)
Wall shear rate (WSR) is an important stimulus for the brachial artery flow-mediated dilation (FMD) response. However, WSR estimation near the arterial wall by conventional Doppler is inherently difficult. To overcome this limitation, we utilized multigate Doppler to accurately determine the WSR stimulus near the vessel wall simultaneously with the FMD response using an integrated FMD system [Ultrasound Advanced Open Platform (ULA-OP)]. Using the system, we aimed to perform a detailed analysis of WSR-FMD response and establish novel WSR parameters in a healthy young population. Data from 33 young healthy individuals (27.5 ± 4.9 yr, 19 females) were analyzed. FMD was assessed with reactive hyperemia using ULA-OP. All acquired raw data were postprocessed using custom-designed software to obtain WSR and diameter parameters. The acquired velocity data revealed that nonparabolic flow profiles within the cardiac cycle and under different flow states, with heterogeneity between participants. We also identified seven WSR magnitude and four WSR time-course parameters. Among them, WSR area under the curve until its return to baseline was the strongest predictor of the absolute (R(2) = 0.25) and percent (R(2) = 0.31) diameter changes in response to reactive hyperemia. For the first time, we identified mono- and biphasic WSR stimulus patterns within our cohort that produced different magnitudes of FMD response [absolute diameter change: 0.24 ± 0.10 mm (monophasic) vs. 0.17 ± 0.09 mm (biphasic), P < 0.05]. We concluded that accurate and detailed measurement of the WSR stimulus is important to comprehensively understand the FMD response and that this advance in current FMD technology could be important to better understand vascular physiology and pathology. NEW & NOTEWORTHY An estimation of wall shear rate (WSR) near the arterial wall by conventional Doppler ultrasound is inherently difficult. Using a recently developed integrated flow-mediated dilation ultrasound system, we were able to accurately estimate WSR near the wall and identified a number of novel WSR variables that may prove to be useful in the measurement of endothelial function, an important biomarker of vascular physiology and disease.